Lacustrine low-temperature dolomite of Oligocene, northern Tibetan Plateau, NW China: Insights from C-O-Mg isotope constraints - Yizhe Wang; Hairuo Qing; Long Li; Yanan Fang; Jason Cosford; Dayou Chen; Huining Wu; Chaodong Wu (Journal of Asian Earth Sciences, 2025)

δ26Mg-δ13C-δ18O systems as geochemical tracers for dolomite recrystallization: A case study of lower Ordovician dolomite from Tarim Basin - Hairuo Qing; Zhanfeng Qiao; Siyang Zhang; Jason Cosford; Anping Hu; Feng Liang; Yongsheng Wang; Jianfeng Zheng (Chemical Geology, 2023)

Mid‐elevation ecosystems of Panama: future uncertainties in light of past global climatic variability - Alexander Correa‐Metrio; Maria I. Vélez; Jaime Escobar; Jeannine‐Marie St‐Jacques; Minerva López‐Pérez; Jason Curtis; Jason Cosford (Journal of Quaternary Science, 2016)
Modern changes in regional climates will result in high ecosystem turnover and substantial biodiversity rearrangements. Understanding these changes requires palaeoecological studies at temporal resolutions comparable to the time window at which modern climate change is occurring. Here we present a multi‐proxy, high‐resolution record of forest and lake ecosystem change that occurred during the last 1100 years at middle elevations in Panama. From ∼900 to 1400 CE, regional forest and lake ecosystems were characterized by high seasonality, probably associated with both high El Niño activity and higher global temperatures. At ∼1400 CE, an abrupt transition marked the decoupling of forest and lake responses, with forest responding mostly to local patterns of human occupation, and lake trophic status being controlled mostly by the regional precipitation–evaporation balance, possibly associated with solar irradiance. Factors that played important roles in shaping regional ecosystems during the last 1100 years will probably again play critical roles within the coming decades, i.e. higher precipitation seasonality and higher temperatures. Past responses of the system, together with pervasive human activities, suggest that future conditions will simplify mid‐elevation forests. Given the importance of these geographical locations as hotspots of biological diversity, substantial losses of global biodiversity are foreseen.